The Relationship Between Body Dissatisfaction and Social Anxiety in Adolescents Using Instagram Face Filter - Apriliana, Vionita; Suratmini, Dwi (Universitas Airlangga, 2024)
Introduction: Dissatisfaction with one’s body, especially the face, is common among adolescents. These feelings often lead young women to use face filters on Instagram to conceal their feelings. The gap between real-life appearances and virtual images can increase anxiety in social situations. This study aimed to investigate the relationship between body dissatisfaction and social anxiety among adolescent girls who utilize face filters on Instagram. Method: This research employed an observational analytic correlation design with a cross-sectional approach involving a sample of 165 participants selected through purposive sampling. The level of body dissatisfaction was assessed using the Multidimensional Body-Self Relations Questionnaire-Appearance Scale, which yielded a Cronbach Alpha reliability coefficient of 0.866. Meanwhile, social anxiety levels were measured using the Social Anxiety Scale for Adolescents, which demonstrated a Cronbach Alpha reliability coefficient ranging from 0.76 to 0.91. Results: The univariate analysis showed that 24.2% of respondents had moderate body dissatisfaction, while 52.7% experienced average social anxiety. The bivariate analysis revealed a strong positive correlation (r=0.435**, p=0.001) between body dissatisfaction and social anxiety, indicating that increased body dissatisfaction is associated with higher social anxiety levels. Conclusions: The findings suggest a significant relationship between body dissatisfaction and social anxiety among adolescent girls who use face filters on the Instagram platform. It is recommended that health education initiatives be implemented for young Instagram users to help mitigate body dissatisfaction and anxiety in their social interactions.